Academics’ Experiences during Horrible Times: Online Teaching, Learning, and COVID-19 - Mohammed Xolile Ntshangase; Zime Pride Zulu (Journal of Research in Education and Pedagogy, 2024)
E-Learning has become the new normal in Higher Educational Institutions across South Africa. Hence, intergration of the new learning pedagogies has initiated a shift of the norms on professional development. This paper seeks to unpack the strategies used by lecturers in the face of adversities experienced during the E-learning space pre & post Covid-19. There are strategies advised by teacher autonomy which need to be explored. It might have been better if teacher autonomy was merely being against pressures exerted on the individual teachers. But, it is a means for teachers to advance their personal and professional capability to adapt to the rapidly changing conditions and situations in learning spaces. This paper seeks to unravel an unacquainted new path on the drive of lecturers in their professional development that has not been evident in their training. In socio-politically transforming societies such as South Africa, the absence of adequate structures to implement a range of changing policies, may leave lecturers in despair when trying to access development opportunities. This paper adopts analytic theory and semi-structured interviews to give light to the constructivist views of lecturers who have developed methods during the times of adversity. Purposive sampling of 6 lecturers and 10 students will help the generation of data for this study because even though lectures had to adjust to new methods but students were in the receiving end of all the pressure. This study argues for implementation of best practices for the successful professional development of academics in line with E-learning. The University of Limpopo will be the centre of data generation with ethical considerations requested as well as literature visited. Collected data will be thematically analysed in order to sieve and arrange the necessary information for this study. The newly shared practices will form part of the resolutions to the professional development of academic staff.